Fostering linking social capital for successful agricultural development projects in South Africa. Issue 1 (2nd January 2017) - Taruvinga, Bridget; Ndou, Portia; Hlerema, Igenecious Nicholas; Maraganedzha, Thetshelesani Lesly; Du Plooy, Christian Philippus; Venter, Sonja
ABSTRACT: This study investigated the importance of linking social capital in agricultural development projects by analysing responses from 205 farmers involved in sweet potato, medicinal plants and African leafy vegetables enterprise development projects in South Africa. Results of the study indicated that linking social capital relationships in farming opened opportunities for farmers to receive implements, production inputs and training. Findings from the Binary logistic regression model revealed that elements of social capital, namely flow of resources, quality of information, cooperation, trustworthiness and inclusion in decisions are important predictors of enterprise success. Strategies of fostering linking social capital that were recommended in the study include gathering enough information which assist in setting achievable targets, formulating a strategy for resource procuring and delivering, and formulating a standardised system for verifying training material and other information media for simplicity. Sharing project vision information with beneficiaries and engaging them in decision making were also recommended.